Ergonomic Risk Analysis with Complaints of Musculoscletal Disorders in Red Brick Workers - Eka Saul Manunel; R. Azizah; H. J. Mukono; Luh Putu Ruliati; Soleman Landi (Sarana Ilmu Indonesia (salnesia), 2022)
Disorders that occur in the skeletal muscles that are felt by individuals ranging from mild to very severe complaints, namely Musculoskeletal Disorders. MSDs complaints can be caused by incorrect work position or attitude, exposure to vibrations, repeated heavy lifting of weights, bending, prolonged sitting, geometry of the spinal lumbar canal and others. This study aimed to determine musculoskeletal complaints in red brick new workers and the factors that influence them. This research method uses descriptive analytic research with a cross sectional approach. The research was conducted in February 2021 in Tanah Putih Village, Kupang Regency, with 40 red brick workers. The independent variable of this research was ergonomic risk and the dependent variable is musculoskeletal disorders. The measuring tool used the nordic body map and a questionnaire. The first step was the creation of a questionnaire in the form of a table containing a list of body parts and a dichotomous scale for pain assessment. Data analysis technique used chi square. The results showed that there were three factors causing musculoskeletal disorders and the two factors had no relationship. Years of work, smoking behavior, work attitudes, working hours have a relationship with musculoskeletal disorders, whereas age and workload have no relationship with musculoskeletal disorders. Suggestions in research for new red brick workers must pay attention to and improve their work attitude, so they can avoid musculoskeletal complaints.